Safety profile of Dioscorea hispida tuber extract: a combined acute toxicity and genotoxicity study - Muhammad, Hussin; Nik Zainuddin, Nik Aina Syazana; Md Nasir, Nur Liana; Ab Dullah, Siti Soleha; Ibnu Rasid, Elda Nurafnie; Lau, Mei Siu; Abd Rahman, Mohd Rahimi Ashraf; Poo, Chin Long; Mustapha Kamal, Siti Khadijah; Awang, Norizah (Frontiers in Pharmacology, 2025)
IntroductionDioscorea hispida has been widely known for consumption as food due to its medicinal properties. The present study evaluated the safety of D. hispida tuber aqueous extract through single-dose toxicity and genotoxicity assessments. MethodsAn acute oral toxicity study was conducted with single oral doses of 5, 50, 300, and 2000 mg/kg body weight D. hispida aqueous extract in respective groups. The bacterial reverse mutation test was performed on Salmonella typhimurium strains TA100, TA1535, TA98, TA1537, and Escherichia coli strain WP2uvrA using the pre-incubation method, both in the presence and absence of an exogenous metabolic activation system (S9). An in vitro micronucleus assay was carried out on V79B cells, a fibroblast-like cells. The cells were treated with D. hispida aqueous extract at concentrations of 1.25, 2.5, and 5 mg/ml, along with positive or negative controls (distilled water). The cells were stained with acridine orange, observed under a fluorescence microscope, and scored for micronuclei.ResultsOur findings showed the administration of D. hispida aqueous extract did not cause any adverse effects up to 2000 mg/kg body weight. Additionally, D. hispida aqueous extract did not induce mutagenicity in tested Salmonella and E. coli tester strains and did not increase revertant colonies at concentrations up to 5000 μg/plate. No significant changes were observed in the number of micronucleated cells compared to the untreated group.DiscussionD. hispida aqueous extract is not toxic in both in vivo acute toxicity and in vitro genotoxicity studies. However, further investigations are needed for preclinical studies on repeated administration and in vivo genotoxicity assays.